A Digital Literacy and Pedagogical Transformation: A Case Study of Teachers’ Training in Remote Areas - Sujariati; Mallapiang, Yassir; Ika Sastrawati (Universitas Veteran Bangun Nusantara, 2025)
With a focus on SMA Negeri 16 Gowa and SMP Negeri 1 Parigi Gowa, this study investigates how digital literacy aids in pedagogical transformation in rural schools. In order to support pedagogical transformation in rural schools, the main goals were to investigate the digital literacy of teachers, the efficacy of training programs, the difficulties in implementing digital learning, and potential models and solutions. A purposive sample of twelve teachers was used in a qualitative case study design. Semi-structured interviews, document reviews, and classroom observations were used to gather data. Teachers' abilities, experiences, and reflections were recorded by the instruments, and thematic analysis was used to examine the data. The results showed that although teachers have rudimentary to intermediate digital skills, they still hardly ever use sophisticated tools for interactive instruction. Because programs were frequently short-term and not adapted to local needs, existing training increased awareness but did not result in meaningful changes. Teachers also mentioned issues like inadequate devices, poor internet access, inadequate infrastructure, and low student engagement. The results of document analysis and interviews suggested that context-sensitive, mentoring-based training models would work better than one-time workshops. Teachers also offered doable fixes, such as bettering the infrastructure, collaborating with the community, and focusing professional development more locally. By emphasizing the significance of contextualizing digital literacy in rural education, this study makes a theoretical contribution. In a practical sense, it provides direction for educators and legislators in creating efficient support and training programs. It demonstrates how improved digital proficiency can support more engaging and globally relevant English language instruction in rural Indonesian classrooms.